2017
DOI: 10.1021/acsami.7b13694
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Synthesis of GaN Driven by Kinetic Energy beyond the Limit of Thermodynamics

Abstract: The nitridation reaction is significantly important to utilize the unique properties of nitrides and nitrogen-doped materials. However, nitridation generally requires a high temperature or highly reactive reagents (often explosive) because the energies of N-N bond cleavage and nitrogen anion formation (N) are very high. We demonstrate the first room-temperature synthesis of GaN directly from GaCl by nanoscale atom exchange reaction. Nonequilibrium nitrogen molecules with very high translational energy were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Group III nitride semiconductors have drawn considerable attention in the past few decades because of their outstanding properties that lead to a variety of applications in electronics and optoelectronics. Among these semiconductor materials, gallium nitride (GaN) is the most studied target since it possesses many advantages of properties including high room-temperature electron mobility (∼10 3 cm 2 V –1 s –1 ), wide band gap (∼3.4 eV), and large short-wavelength absorption coefficient, which makes it an important semiconductor for device applications in light emitting diodes, field effect transistors, solar cells, lasers, photodetectors, and high-speed optoelectronic devices. With the development trend of device minimization and integration, low-dimensional GaN nanomaterials such as nanowires, nanotubes, and nanosheets have attracted more and more interest due to the advantages of their structures and potential properties with respect to their bulk counterpart. In particular, two-dimensional (2D) GaN materials are expected to be realized for optoelectronic applications due to the success of atomically thin graphene and transition metal dichalcogenides (TMDs). Hence, great efforts are devoted to the synthesis of 2D GaN materials, and they have been synthesized experimentally with thicknesses from dozens of nanometers to several atomic layers. , However, the structure of 2D GaN is still under debate. It is widely acceptable that the ultrathin GaN nanosheets with the wurtzite (WZ) phase are unstable and tend to transform into a graphitic (GP) phase. , Recent theoretical studies have found that few-layer GaN nanosheets can reconstruct into a haeckelite (HK) phase with alternating octagonal and square rings. , Therefore, the understanding of size effect on fundamental structural and electronic properties of GaN nanosheets is essential for their device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Group III nitride semiconductors have drawn considerable attention in the past few decades because of their outstanding properties that lead to a variety of applications in electronics and optoelectronics. Among these semiconductor materials, gallium nitride (GaN) is the most studied target since it possesses many advantages of properties including high room-temperature electron mobility (∼10 3 cm 2 V –1 s –1 ), wide band gap (∼3.4 eV), and large short-wavelength absorption coefficient, which makes it an important semiconductor for device applications in light emitting diodes, field effect transistors, solar cells, lasers, photodetectors, and high-speed optoelectronic devices. With the development trend of device minimization and integration, low-dimensional GaN nanomaterials such as nanowires, nanotubes, and nanosheets have attracted more and more interest due to the advantages of their structures and potential properties with respect to their bulk counterpart. In particular, two-dimensional (2D) GaN materials are expected to be realized for optoelectronic applications due to the success of atomically thin graphene and transition metal dichalcogenides (TMDs). Hence, great efforts are devoted to the synthesis of 2D GaN materials, and they have been synthesized experimentally with thicknesses from dozens of nanometers to several atomic layers. , However, the structure of 2D GaN is still under debate. It is widely acceptable that the ultrathin GaN nanosheets with the wurtzite (WZ) phase are unstable and tend to transform into a graphitic (GP) phase. , Recent theoretical studies have found that few-layer GaN nanosheets can reconstruct into a haeckelite (HK) phase with alternating octagonal and square rings. , Therefore, the understanding of size effect on fundamental structural and electronic properties of GaN nanosheets is essential for their device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an optimum energy exists for bond selective formation to proceed. Pyridinic nitrogen formation is rich under higher beam energy (12 eV) …”
Section: Resultsmentioning
confidence: 99%
“…12 Moreover, GaN monolayers have been synthesized in experiments. [13][14][15][16] The research of the current paper provides a new way to investigate the GaNGeC system from bulk materials to thin films, the doublelayer vdW heterojunction and single-layer.…”
Section: Electronic Band Structures Elastic Constants and Optical Spmentioning
confidence: 99%
“…12 GaN monolayers have been synthesized in experiments. [13][14][15][16] Moreover, threedimensional (3D) GaN has excellent electronic and optical properties, as a typical representative of third-generation semiconductors, and has been widely used in microwave communications, light-emitting diodes and laser diodes in the ultraviolet range. Recently, GaCN and GeCN ternary compounds, such as Ga 2 (CN 2 ) 3 and GeCN 2 had been predicted by the calculations from Materials Project.…”
Section: Introductionmentioning
confidence: 99%